The Philosophy of Sharia Muamalah: Between Slavery to God and Economic Development: فلسفة الاقتصاد الإسلامي: بين العبودية لله والتنمية الاقتصادية - Mariam Elbanna; Suparman Syukur (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to explore the intrinsic relationship between the philosophy of Islamic economics and the realization of servitude to Allah Almighty, focusing on how economic activities support the achievement of Maqasid al-Sharia and sustainable economic development. Theoretical framework: The theoretical framework is based on the principle that wealth is a trust from Allah that must be managed according to Sharia guidelines to balance material and spiritual needs. Literature Review: The literature review examines the role of Sharia regulations, such as the prohibition of riba, zakat, and charitable giving, in fostering social justice and economic stability. Additionally, the study highlights the concept of stewardship (khalifah) in wealth management, emphasizing the ethical responsibility of individuals to use resources in ways that please Allah. Methods: This research employs a qualitative descriptive approach with a literature review method, incorporating primary and secondary sources on Islamic economics. Data analysis is conducted systematically to identify the relationship between the philosophy of Islamic economics and the application of Sharia values in economic activities. Results: The findings reveal that mechanisms such as the prohibition of riba, zakat, and the concept of khalifah significantly contribute to reducing social inequalities and promoting economic solidarity. Furthermore, Islamic economics encourages ethical innovation, halal production, and sustainable development through balanced resource utilization. Implications: The study's implications emphasize the need to strengthen Sharia-based policies to support sustainable development goals and foster a just and cohesive society. Novelty: The novelty of this study lies in the integration of the philosophy of Islamic economics, ethical wealth management, and sustainable development orientation, providing a comprehensive perspective on applying Sharia values in the modern economic context.